Interim results of a real-world observational study of eribulin in soft tissue sarcoma including rare subtypes. (31st July 2019) - Kobayashi, Eisuke; Naito, Yoichi; Asano, Naofumi; Maejima, Aiko; Endo, Makoto; Takahashi, Shunji; Megumi, Yasunori; Kawai, Akira
Abstract : Interim analysis from the first large-scale post-marketing surveillance study of eribulin treatment for soft tissue sarcomas (STSs) showed antitumor activity in both common and rare subtypes of STS (NCT03058406). Abstract: Background: Although eribulin is used to treat soft tissue sarcomas (STSs), treatment data for rare subtypes are limited. We conducted a post-marketing surveillance study to assess safety and efficacy of eribulin in STS patients stratified by subtype. Methods: Japanese patients ( n = 256) with advanced or metastatic STS receiving eribulin treatment were monitored for treatment status, adverse events, diagnostic imaging, and clinical outcomes at 3 months and 1 year. Interim analysis was performed. Patients will be monitored up to 2 years. Results: Interim analysis included 3-month ( n = 255), imaging ( n = 226), and 1-year ( n = 105) data. STS subtype distribution was normal. Median number of eribulin cycles was 3.0 (range: 1–17 cycles). Among patients with imaging data, best overall tumor response (12 weeks) was partial response, 7.5% ( n = 17); stable disease, 34.5% ( n = 78); and stable disease ≥11 weeks, 10.2% ( n = 23). Overall response rate (ORR), disease control rate (DCR), and clinical benefit rate (CBR) for all patients were 7.5%, 42.0% and 17.7%, respectively. ORR, DCR, and CBR were 10.3%, 32.0% and 16.5%, respectively, for patients with STS subtypes other than liposarcoma and leiomyosarcoma and included responses from patients with rare STS subtypes. Adverse drug reactions (ADRs) occurred in 211 (82.7%) patients (42 [16.5%] patients had serious ADRs), and none led to death. ADRs leading to drug withdrawal and dose reduction occurred in 27 (10.6%) and 55 (21.6%) patients, respectively. Conclusion: Eribulin was generally well tolerated and showed antitumor activity against STSs, including rare subtypes that currently have few treatment options. Clinical trial number: NCT03058406 (ClinicalTrials.gov)